ASSESSMENT OF FACTORS ASSOCIATED WITH THE REFUSAL OF RECOMMENDED THRICE A WEEK DIALYSIS IN CKD PATIENTS: REALITY VERSUS RECOMMENDATIONS - GULZAR, A; RAFIQUE, Z; AFZAL, A; IMRAN, S; ISRAR, A; NASIM, A (Biological and Clinical Sciences Research Journal, 2022)
In developing countries like Pakistan, it is observed that the patients who are on dialysis do not follow the prescribed frequency of dialysis which has increased the morbidity, mortality, and burden on nephrology emergencies. To identify the most common factors associated with the refusal of recommended thrice-a-week dialysis. This observational study was carried out between June 1 and August 14, 2022, in the Department of Nephrology and Hemodialysis at the Services Hospital Lahore. The WHO calculator (version 1.1) was used to determine the sample size of 137. The patients in this study comprised those on maintenance twice-weekly hemodialysis who were anuric and advised for thrice-weekly dialysis but declined it. The senior faculty of the nephrology unit created a form with demographic information and a questionnaire to evaluate the likely reasons. The reason was categorized into three categories including socioeconomic psychology and healthcare-related factors. Using the program SPSS, the data was examined (V. 25). Mean and median were used to describe quantitative factors, and frequency or percentage were used to convey qualitative data. Based on the inclusion criteria, a total of 137 people were included in this study. 62% of the sample in our study were men. Our cohort’s median age was 49.54 ± 9.50 years. 52% of the participants were in the 36 to 55 age range. 68 % of the patients who declined three times weekly dialysis were married. Only 28% of patients had higher education, while only 46% had a high school diploma and 19% had none at all. 71% of the people in our research were employed, yet the majority made less than twenty thousand PKR per month. Among the healthcare-related factors, the most common factor was the unavailability of dialysis centres (66.2%). From the results of the study, we can conclude that the lack of education and support from the organization they work for, increase responsibilities after married, low socioeconomic status and inadequate healthcare facilities are the major hurdle in compliance for advised thrice a week dialysis. These factors along with the nature of disease cause many psychological problems that further worsen the situation.